A Giant Gastroschisis Associated with Pulmonary Hypoplasia and Spinal Anomaly: A Case Report and a Literature Review. (2nd May 2018) - Puvabanditsin, Surasak; Burger, Robin; Puthenpura, Vidya; Walzer, Lauren; Madubuko, Adaora; Minerowicz, Christine; Mehta, Rajeev
Abstract : Gastroschisis most often occurs as an isolated anomaly and extragastrointestinal associations are rare. Most commonly, the anomalies associated with gastroschisis are cardiac and central nervous system abnormalities. Respiratory insufficiency has sometimes been reported in association with giant abdominal wall defects. Poor outcomes and prolonged ventilator support have been reported in giant gastroschisis and omphalocele, especially if associated with herniation of the majority of the liver. We report a case of a large gastroschisis that was associated with a kyphoscoliosis and pulmonary hypoplasia.